Molecular Subtyping of Salmonella enterica Serovar Paratyphi B from Animal and Food Isolates in Malaysia - Yee-Ling, Goh,; Jamli, Maria; Kwai-Lin, Thong, (Malaysian Journal of Science, 2003)
The genetic diversity of 16 animal and food strains of $Salmonella$ $enterica$ Paratyphi B from different animal hosts between the years 1979-2001 was determined by pulsed-field gel electrophoresis (PFGE), ERIC-PCR and REP-PCR analysis. Fourteen isolates were tested positive for dextrorotary-tartrate tests (S. Paratyphi B dT+, also known as S. Java) while two were d-tartrate negative (S. Paratyphi B dT-). Most of the strains tested were sensitive to the commonly used antibiotics. Both REP-PCR and ERIC-PCR gave five different profiles with a diversity index (DI) of 0.67 and 0.69 respectively. PFGE of XbaI digested chromosomal DNA from these isolates showed that there was a high degree of heterogeneity (F= 0.59-1.0) and most of the strains had unique profiles with a DI of 0.99. Strains that were isolated from different sources and years were genetically distinct. A pair of S. Paratyphi B dT+ strains isolated from cattle and pheasant were similar, indicating that these two different animals were probably infected with the same strain. A dendrogram based on the unweighted pair group average method (UPGMA) algorithm showed that the bovine isolates recovered from cattle in 1984 were in one cluster indicating that the strains were probably derived from a single clone. PFGE is more discriminative that PCR-based methods in determining the clonality and genetic diversity of Salmonella Paratyphi B. To the best of our knowledge, this is the first study to report the genetic variation of chromosomal $S.$ $enterica$ Paratyphi B var Java from animal and food in Malaysia.